Triple combination of vemurafenib, cobimetinib, and atezolizumab in real clinical practice in the Russian Federation: results of the A1 cohort of the ISABELLA study - Samoylenko, Igor V.; Kolontareva, Yulia M.; Kogay, Ekaterina V.; Zhukova, Natalia V.; Utyashev, Igor A.; Ivannikov, Mikhail E.; Menshikov, Konstantin V.; Zinkevich, Maxim V.; Orlova, Kristina V.; Vakhabova, Yulia V.; Volkonsky, Mikhail V.; Beliaeva, Natalia A.; et al. (Frontiers in Oncology, 2024)
BackgroundAmong several treatment options for BRAF-mutant metastatic melanoma, a combination of BRAF inhibitor, MEK inhibitor, and anti-PDL1 antibody seems to be a new emergent approach recently registered in the Russian Federation. It is still not clear which patient population benefits more from this simultaneous use of three drugs instead of its sequencing.AimThis study aimed to evaluate patients’ characteristics treated in real practice in 14 Russian regions by triple combination and to analyze their outcomes depending on biomarkers (PD-L1 expression).MethodsThis was a part (cohort A1) of a prospective non-interventional study of clinical outcomes and biomarkers in patients with skin melanoma. Patients were included in cohort A1 if combination treatment with vemurafenib (vem) + cobimetinib (cobi) + atezolizumab (atezo) was initiated no earlier than 12 weeks (84 days) prior to written informed consent to participate in this study. The index event was the initiation of therapy with all three drugs vem + cobi + atezo (i.e., triple combination). The primary efficacy endpoint of the study was the 24-month overall survival (OS), defined as the time from the index date to the date of death from any cause. If the patient did not experience an event, the OS will be censored at the date of the last contact. Objective response rate (ORR), duration of response (DoR), and progression-free survival (PFS) in the Intention to treat (ITT) population, in biomarker positive population, and in population with brain metastases were also evaluated. Quality of life questionnaires were pre-planned by protocol if it was a part of routine practice. Adverse events were also collected.ResultsBetween March 2021 and May 2023, 59 patients were enrolled in 19 centers from 14 regions of Russia. Thirty-one of 59 (52.4%) patients had central nervous system metastases, and 18 of 31 (58.4%) were symptomatic. Forty of 59 patients (68%) received the triple combination as the first-line treatment. The median follow-up period was 16.83 [95% confidence interval (CI) 13.8–19.8] months. The mean duration of therapy with this regimen was 9.95 months (95% CI 7.48–13.8). ORR was 55.1%; progression as the best outcome was seen in 16.3%. The median DoR was 12.95 months (95% CI 11.0–14.8 months), with a median of 20.3 months (95% CI 9.1–31.5 months) when triple therapy was administered in the first-line treatment. In patients with brain metastases (N = 31), ORR was 45.1%; the median DoR was 12.95 (95% CI 11.0–14.8 months). The median PFS in the entire population was 13.6 months (95% CI 8.6–18.6); the 24-month PFS was 22%. The estimated median OS in the entire population was 15.8 months (95% CI NA); 24-month OS was 45% (95% CI 0.32–0.64). In multivariate Cox regression model, biomarkers of interest [lactate dehydrogenase, Programmed cell death ligand-1 (PD-L1)] did not have statistically significant impact on PFS, OS, or DoR probably due to high data missing rate. No unexpected adverse events were reported. Grades 3–4 AEs were seen in 23 of 59 patients (38%) with most common were skin and liver toxicity.ConclusionTriple combination of atezolizumab, vemurafenib, and cobimetinib had proven its efficacy and tolerability in real settings. No impact of potential predictive biomarkers was seen (NCT05402059).